2020
DOI: 10.1061/(asce)gt.1943-5606.0002357
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Hydraulic Conductivity Model for Unsaturated Soils at Low Degree of Saturation and Its Application to the Study of Capillary Barrier Systems

Abstract: (2020) 'Conceptual hydraulic conductivity model for unsaturated soils at low degree of saturation and its application to the study of capillary barrier systems.', Journal of geotechnical and geoenvironmental engineering., 146 (10). 04020106.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…reduces to the "bulk water-continuity value" of the coarser layer, at which the hydraulic conductivity of the C.L. starts increasing significantly (Scarfone et al, 2020). At this point, water breakthrough occurs from the F.L.…”
Section: Drying)mentioning
confidence: 95%
See 3 more Smart Citations
“…reduces to the "bulk water-continuity value" of the coarser layer, at which the hydraulic conductivity of the C.L. starts increasing significantly (Scarfone et al, 2020). At this point, water breakthrough occurs from the F.L.…”
Section: Drying)mentioning
confidence: 95%
“…He demonstrated this by presenting hysteretic versions of the modified Brooks and Corey (modBC) and modified Kosugi (modK) SWRC models described earlier. Scarfone et al (2020) recently showed that the conventional Mualem (1976) model, following the general approach adopted by Peters (2013), the hydraulic conductivity kl can be split into two components:…”
Section: Scanning Retention Curvesmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerical analyses were conducted by Rahardjo et al [22] to determine the thickness and length of the fine-and coarse-grained materials of the capillary barrier system. Scarfone et al [23,24] used advanced numerical modeling to extensively study the effectiveness of capillary barrier systems in introducing water retention hysteresis into the hydraulic behavior of unsaturated soils, considering a new hydraulic conductivity model at a low degree of saturation, and the complex phenomenon of soil-atmosphere interaction in the long term.…”
Section: Introductionmentioning
confidence: 99%